MENINGKATKAN MUTU ASN IHDN DENPASAR DENGAN PELAYANAN PUBLIK BERBASIS TAT TWAM ASI - Wariati, Ni Luh Gede (LPM IHDN Denpasar, 2016)
The understanding and application of ethical values are essential in providing excellent service to the community. One kind of success of an institution is when it is able to provide excellent service to the community. Tat TvamAsi is one ofHindu philosophies that is loaded with ethical or moral values, it means that